1967
DOI: 10.1111/j.1365-2141.1967.tb08728.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Creatine in Red Cells

Abstract: SUMMARY The creatine in packed red cells was estimated by the diacetyl‐i‐naphthol technique. The error due to the presence of other guanidino compounds in the cells was found to be small. The mean value for creatine in the packed red cells of normal females was found to be 5.6 (S.D. ± 1.3) mg. per 100 ml., and in normal males 4.4 (S.D. ± 1.5) mg. per 100 ml. The sex difference is statistically significant. When red cells were segregated according to age by centrifugation the young red cells contained more crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 11 publications
3
44
0
Order By: Relevance
“…First, the Ca2-influtx correlates well with percentage of' reticuilocvtes ( Fig. 3) btut this flutx does not correlate with ervthrocyte creatine which reflects the ImleaIn cell age (13,20).…”
Section: Resultsmentioning
confidence: 99%
“…First, the Ca2-influtx correlates well with percentage of' reticuilocvtes ( Fig. 3) btut this flutx does not correlate with ervthrocyte creatine which reflects the ImleaIn cell age (13,20).…”
Section: Resultsmentioning
confidence: 99%
“…13,14) Because young erythrocytes contain higher erythrocyte creatine levels than older erythrocytes which decrease with advancing age, erythrocyte creatine is regarded as a reliable and quantitative marker to estimate the mean age of the erythrocyte. 8,9) In our earlier report, we measured erythrocyte creatine with other hemolytic markers to detect intravascular hemolysis in patients with a prosthetic valve and found that erythrocyte creatine was the most reliable marker to detect intravascular hemolysis. 4) Moreover, mild hemolysis was related to an increase in valvular flow velocity rather than valvular regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, erythrocyte creatine is regarded as a sensitive and quantitative marker of mean age of the erythrocytes, because creatine contents in erythrocytes decrease gradually with advancing cell age and an increase in erythrocyte creatine quantitatively reflects the degree of shortened erythrocyte survival. [8][9][10] In our previous report, we measured erythrocyte creatine in patients with cardiac valve prostheses and found that erythrocyte creatine was a sensitive marker to detect intravascular hemolysis. 4) Intracardiac high velocity jets through stenosed or incompetent orifices can cause intravascular hemolysis, but few case reports have evaluated intravascular hemolysis in patients with native valvular heart disease.…”
Section: Ntravascular Hemolysis Has Been Identified In Patients Withmentioning
confidence: 99%
“…To support the hypothesis of a delay in reticulocyte maturation, Sher et al [4]were able to demonstrate that the red cell creatine content was only slightly increased in their patient. Since the red cell creatine content is inversely proportional to the age of red cells, a real increase in reticulocyte production should be associated with an increase in red cell creatine values [8]. …”
Section: Discussionmentioning
confidence: 99%